Legal Pluralism in Postcolonial Nations: Reconciling Customary, Religious, and State Norms in Judicial Practices - James Kirunda; Helen Nabirye; Ronald Muwanguzi (Rechtsnormen: Journal of Law, 2025)
Background. Postcolonial nations often grapple with the coexistence of multiple legal systems, including state law, customary norms, and religious legal traditions. This legal pluralism reflects historical layers of colonization, indigenous governance, and religious authority, yet it frequently results in normative conflicts within judicial processes. Courts are regularly confronted with cases that require navigating overlapping legal frameworks, raising questions about authority, legitimacy, and the equitable treatment of diverse legal subjects. Purpose. This study aims to critically examine how postcolonial judicial systems reconcile these competing normative orders in practice. Method. Employing a comparative socio-legal methodology, the research analyzes judicial decisions and legal frameworks from Indonesia, Nigeria, and India countries characterized by entrenched plural legal structures. Results. The findings reveal that while legal pluralism is often constitutionally acknowledged, its practical implementation is marked by selective incorporation, strategic ambiguity, and jurisdictional contestation. Courts act as sites of normative negotiation, where customary and religious laws are either validated, reinterpreted, or subordinated to state law. Conclusion. The study concludes that achieving legal coherence in postcolonial contexts requires more than doctrinal reform; it demands a rethinking of legal authority that embraces pluralism while safeguarding human rights and procedural fairness.